2017
DOI: 10.1016/j.celrep.2017.10.084
|View full text |Cite
|
Sign up to set email alerts
|

Capture of Dense Core Vesicles at Synapses by JNK-Dependent Phosphorylation of Synaptotagmin-4

Abstract: SummaryDelivery of neurotrophins and neuropeptides via long-range trafficking of dense core vesicles (DCVs) from the cell soma to nerve terminals is essential for synapse modulation and circuit function. But the mechanism by which transiting DCVs are captured at specific sites is unknown. Here, we discovered that Synaptotagmin-4 (Syt4) regulates the capture and spatial distribution of DCVs in hippocampal neurons. We found that DCVs are highly mobile and undergo long-range translocation but switch directions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
59
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(64 citation statements)
references
References 55 publications
4
59
1
Order By: Relevance
“…Possibly, activity causes a redistribution of DCVs but no proper recruitment at release sites occurs, thus DCVs may be ‘dropped’ in these regions of the axon when no synapsin-based tethering of DCVs to the actin cytoskeleton can occur. This supports two conclusions: 1) Contrary to previous publications that attributed ‘capture’ merely to a tightly regulated balance of antero- and retrograde molecular motors of the tubulin cytoskeleton (Bharat et al, 2017; Morrison et al, 2018; Stucchi et al, 2018), our data suggest that also a direct tethering of DCVs occurs by synapsin, as established for SVs, to keep them near synaptic release sites. 2) This process appears to depend on S9, where phosphorylation leads to release of the captured DCVs from the actin cytoskeleton to enable their PM localization and fusion.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Possibly, activity causes a redistribution of DCVs but no proper recruitment at release sites occurs, thus DCVs may be ‘dropped’ in these regions of the axon when no synapsin-based tethering of DCVs to the actin cytoskeleton can occur. This supports two conclusions: 1) Contrary to previous publications that attributed ‘capture’ merely to a tightly regulated balance of antero- and retrograde molecular motors of the tubulin cytoskeleton (Bharat et al, 2017; Morrison et al, 2018; Stucchi et al, 2018), our data suggest that also a direct tethering of DCVs occurs by synapsin, as established for SVs, to keep them near synaptic release sites. 2) This process appears to depend on S9, where phosphorylation leads to release of the captured DCVs from the actin cytoskeleton to enable their PM localization and fusion.…”
Section: Discussionsupporting
confidence: 83%
“…Little is known about proteins mediating DCV capture, however, the process appears to be regulated in an activity-dependent fashion, and was shown to involve fragile-X mental retardation-like protein (FMRP) in flies (Cavolo et al, 2016), as well as synaptotagmin 4. The latter protein was more involved in regulating the interaction of DCV cargo with the microtubule-linked motor proteins kinesin and dynein, thus capture may depend on a tug-of-war between these antero- and retrograde motors (Bharat et al, 2017). However, also actin was found to play a role, such that localization of DCVs at neuronal terminals may involve a handover from microtubules to the actin cytoskeleton.…”
Section: Introductionmentioning
confidence: 99%
“…Knockdown of C9ORF72 expression reduces axonal growth and actin dynamics [ 157 ]. Reduced C9ORF72 levels observed in ALS could affect actin dynamics and thereby, for example, cargo trafficking along the actin cytoskeleton at axonal branches or synapses [ 13 ].…”
Section: Disrupted Axonal Transport In Alsmentioning
confidence: 99%
“…SYT4 is an integral vesicle protein present on brain‐derived neurotrophic factor (BDNF)‐harbouring dense core vesicles (DCVs) in neurons . SYT4 regulates the capture and spatial distribution the DCVs in hippocampal neurons . In a previous study, we found that SYT4 is expressed in mouse melanocytes and B16 melanoma cells…”
Section: Introductionmentioning
confidence: 99%